Clinicopathological Features and Oncological Outcomes of Early and Late Recurrence in Stage III Colorectal Cancer Patients after Adjuvant Oxaliplatin-Based Therapy. (6th January 2023) - Chang, Yu-Tang; Tsai, Hsiang-Lin; Chen, Yen-Cheng; Li, Ching-Chun; Huang, Ching-Wen; Chen, Po-Jung; Su, Wei-Chih; Chang, Tsung-Kun; Yeh, Yung-Sung; Yin, Tzu-Chieh; Wang, Jaw-Yuan
Abstract : Aims . An adjuvant oxaliplatin-based regimen is the standard of care for patients with stage III colorectal cancer (CRC). Few reports have compared the clinicopathological features and oncological outcomes of such treatment between patients with early (≤1 year) and late recurrence (>1 year). Methods . Between January 2012 and December 2019, CRC recurred in 128 (24.1%) of 531 patients with consecutive stage III CRC after they received curative resection and an adjuvant oxaliplatin-based regimen. The clinicopathological features and oncological outcomes of the 128 patients were analyzed retrospectively. Results . The median follow-up period after the first chemotherapy cycle was 35.0 months (range, 7–100.9), and the median recurrence time was 16.1 months. Forty-seven patients (36.7%) had an early recurrence and eighty-one patients (63.3%) had a late recurrence. Compared with patients with late recurrence, those with early recurrence were mostly younger (median: 58 vs. 64 years, p = 0.009 ), had less oxaliplatin-based therapy cycles (median: 8 vs. 12 cycles, p < 0.001 ), and had a shorter overall survival time (median: 23.3 vs. 39.7 months, p < 0.001 ). The area under the curve of patient age and chemotherapy cycles for predicting early recurrence was 0.629 and 0.705 (p = 0.015 and p < 0.001 ), respectively. The receiver operating characteristic curve analysis demonstrated that the cutoff level for patient age was 57 years and the number of chemotherapy cycles was 8. A multivariate analysis revealed that patient age ≤57 years and oxaliplatin-based therapy ≤8 cycles were independent risk factors for early recurrence (odds ratio (OR) = 3.049, p = 0.022 ; OR = 4.995, p = 0.002 ). These factors were associated with an approximately 77.8% risk of recurrence within 1 year, compared with the 21.5% risk associated with patient age >57 years and oxaliplatin-based therapy >8 cycles ( p = 0.003). Conclusion . Patients with early recurrence had poorer survival than those with late recurrence. If >8 cycles of oxaliplatin-based therapy can be administered without disease progression, then patients with stage III CRC would have a lower risk of early recurrence.